HUBUNGAN KARAKTERISTIK IBU DAN PERILAKU DALAM PEMBERIAN MP-ASI DINI DENGAN PERTUMBUHAN BAYI USIA 0-6 BULAN(Studi Di Wilayah Kerja Puskesmas Poncol Kota Semarang Tahun 2017) - Altriza Juliyandari; Suyatno Suyatno; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2018)
The main cause of the occurrence of malnutrition and the obstacles faced growth in children in connection with poor breastfeeding and complementary feeding practices, coupled with high rates of infectious diseases, are the principal proximate causes of malnutrition during the first two years of life.. One of the key constraints in the provision of Breastfeeding because of the behaviour mother itself. Health Profile the City of Semarang 2015 show prevalence of Exclusive Breastfeeding 64,69 % and malnutrition status of 3,54 %. The purpose of this study was to analyzing the relationship of mother variables and early complementary feeding practices to the growth infant's age of 0-6 months in the Work Area of Poncol Community Health Centre. This study was analytic observational with cross sectional designed study. Population in this study was that mother have babies age 0-6 months were amount 291 mother with the total sample 60 mother who were selected with a simple random sampling. Analysis of data used the Pearson Product Moment, Rank Spearman and Chi-Square (p=0.05). The results showed the characteristic of mother most widely 20-30 year old (66,7%), have recent education graduated high school (58,3%), housewive (58,3%), give birth once (46,7%), are in the socioeconomic not poor (81,7%), mother have less and good knowledge (50,0%), attitude of lack (51.7%) and good of practice (68.3%) in early complementary feeding practices. As many as 73.3% of infants decreased in the last 3 months. There was no relationship between age (p = 0,346), parity (p = 0,859) and socioeconomic mother in early complementary feeding practices to the growth of infant's (p = 0,061). There was no relationship between knowledge (p=0,513), attitude (p=0,495) and practice mother in early complementary feeding to the growth of infant's (p= 0,725). There was a relationship between education (p = 0.045) and maternal work in early supplementary feeding for infant growth (p = 0,025). It was concluded that only education and maternal work in early complementary feeding practices to the growth infant's age of 0-6 months.